Esensi dan Eksistensi Alkitab Menurut Ulasan Literatur Biblika Sebagai Hasil Riset Teolog - Marde Christian Stenly Mawikere; Sudiria Hura (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study describes the essence and existence of the Bible according to a review of Biblical literature as a result of research by several theologians. The biblical literature and theological perspectives reviewed are from conservative and contemporary circles who were randomly selected by the researchers in this article. This study uses a qualitative method built by the study of literature that is relevant to the research problem. The final result of this study shows that theologians have different perceptions about the essence and existence of the Bible, but in general they have the same thing that the Bible does not just exist but God's intervention to the writers in the context of history, struggles and struggles of their lives and their communities. For this reason, with varying perceptions, all theologians acknowledge the authority of the Bible in their written Biblical literature. The researchers also point out that there are various strengths and weaknesses in the theologians' perceptions of the problem in question. Thus, it will open the possibility for further research in this field, both scientifically and practically.